﻿ ﻿﻿﻿ 函数的加减 | 玄数
﻿﻿

## 函数的加减

2012-02-15

### 1.   函数的加减（函数的和差）

1.   f (x) = x2 + 3x，g (x) = 2x – 1

.             (f + g) (x) = f (x) + g (x)

.                                 = ( x2 + 3x ) + (2x – 1 )

.                                 = x2 + 5x – 1

.                                 x∈R

2.  f (x) = lg x，g (x) = lg (1 – x2)

.             (f – g) (x) = f (x) – g (x)

.                                 = lg x – lg (1 – x2)

.                                 = lg [x / (1 – x2)]

.                                 x∈ (–∞, –1) ∪ (0,1)

### 2.   函数加、减的图像

1.   f (x) = x2， g (x) = x， (f + g) (x) = x2 + x， (f – g) (x) = x2 – x

3.   f (x) = ex， g (x) = x， (f + g) (x) = ex + x， (f – g) (x) = ex – x

4.   f (x) = lnx， g (x) = x， (f + g) (x) = lnx + x，  (f – g) (x) = lnx – x

5.   f (x) = x2， g (x) = x3，  (f + g) (x) = x2 + x3，  (f – g) (x) = x2 – x3

6.   f (x) = sinx， g (x) = x2， (f + g) (x) = sinx + x2， (f – g) (x) = sinx – x2

7.   f (x) = x2， g (x) = ex，  (f + g) (x) = x2 + ex，  (f – g) (x) = x2 – ex

8.   f (x) = sinx， g (x) = ex，  (f + g) (x) = sinx + ex，  (f – g) (x) = sinx – ex

9.   f (x) = sinx， g (x) = lnx，  (f + g) (x) = sinx + lnx，  (f – g) (x) = sinx – lnx

10.  f (x) = x， g (x) = 1/x，  (f + g) (x) = x + 1/x，  (f – g) (x) = x – 1/x

11.  f (x) = x2， g (x) = 1/x，  (f + g) (x) = x2 + 1/x，  (f – g) (x) = x2 – 1/x

﻿